The invention of enterprise entrepreneurship from ancient Mesopotamia to modern times - Landes, David S.; Mokyr, Joel; Baumol, William J. (Kauffman Foundation series on innovation and entrepreneurship, 2010)
This work provides a sweeping history of enterprise in Mesopotamia and Neo-Babylon; carries the reader through the Islamic Middle East; offers insights into the entrepreneurial history of China, Japan, and colonial India; and describes the crucial role of the entrepreneur in innovation activity in the Western world.
Keywords: Entrepreneurship : History; Unternehmensgründung; BUSINESS & ECONOMICS / Entrepreneurship